Mismatch between anthropometric body dimensions and classroom furniture in Malaysian universities - Aminian, Negin Ozve; Romli, Fairuz Izzudin
The main objective of study is to highlight possible mismatch between the student’s body dimensions and the dimensions of classroom furniture used in most Malaysian universities. This issue is pertinent due to the notable increase in the number of international students who are enrolled in Malaysian universities each year. The matching of body dimensions and classroom furniture is vital to promote proper sitting posture. Body dimensions of the people from the few different countries that are perceived to make up the current student’s population in Malaysia are measured against dimensions of prevalent chairs and desks used in the classroom. The sample case study is done in Faculty of Engineering, Universiti Putra Malaysia but it is believed that the derived conclusion can also be extended to other universities in Malaysia. All in all, several mismatches have been found and highlighted for a better planning and design of classroom furniture.